Elementary Student Knowledge Gains In The Digital Portable Planetarium (Journal of Astronomy & Earth Sciences Education, 2015)
Immersive environments hold promise to provide unique and heightened sensory experiences that focus a learner’s attention, and thus may be useful learning platforms. In particular, portable planetariums may be useful in advancing conceptual knowledge about the night sky, because they afford learners with Earth-based views of celestial motions, give learners a sense of “being there,” and allow direct observation of celestial motions. In this study, we asked whether a digital portable planetarium show would aid students in understanding celestial motions, as well as acquiring generalized astronomy-related knowledge. Results from our pre and post surveys suggest that students make gains in knowledge about both apparent celestial motion and general astronomy concepts after viewing a 25-minute planetarium presentation. Our results suggest that the portable planetarium may be a useful strategy in supporting learners as they struggle with reconciling observed patterns with underlying, non-observable motions of the Earth, and with visualizing concepts such as the speed of planetary orbits relative to their position with respect to the sun.
Keywords: Celestial Motion; Immersive Environments; Planetarium; Conceptual Knowledge